2006
DOI: 10.1186/bcr1399
|View full text |Cite
|
Sign up to set email alerts
|

Classification and risk stratification of invasive breast carcinomas using a real-time quantitative RT-PCR assay

Abstract: IntroductionPredicting the clinical course of breast cancer is often difficult because it is a diverse disease comprised of many biological subtypes. Gene expression profiling by microarray analysis has identified breast cancer signatures that are important for prognosis and treatment. In the current article, we use microarray analysis and a real-time quantitative reverse-transcription (qRT)-PCR assay to risk-stratify breast cancers based on biological 'intrinsic' subtypes and proliferation.MethodsGene sets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(139 citation statements)
references
References 33 publications
5
131
2
1
Order By: Relevance
“…On the contrary, the other group, defined by the opposite pattern of the two markers (high HER2 and low CK8 levels), presented very low or no expression levels of the ER. These data agree with the recently reported molecular classification of breast cancer [20]. Patients with negative or weakly positive ER status and higher expression levels of HER2 presented a worse outcome, in accordance with Perreard et al [20] who found ER-negative tumours more aggressive.…”
Section: Discussionsupporting
confidence: 82%
“…On the contrary, the other group, defined by the opposite pattern of the two markers (high HER2 and low CK8 levels), presented very low or no expression levels of the ER. These data agree with the recently reported molecular classification of breast cancer [20]. Patients with negative or weakly positive ER status and higher expression levels of HER2 presented a worse outcome, in accordance with Perreard et al [20] who found ER-negative tumours more aggressive.…”
Section: Discussionsupporting
confidence: 82%
“…Analysis of gene expression patterns has classified various tumors into distinct clinically and biologically significant subgroups (26)(27)(28)(29). Breast cancer has also been proved to be heterogeneous and is classified into several distinct groups based on the results of gene microarray analysis (10,13,27,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MNAT1 retained significant prognostic value (p ϭ .0006) in the multivariate model, suggesting potential value in assessing prognosis over conventional proliferation markers; however, the value of MNAT1 expression requires independent confirmation. Expression levels of TOP2A and BUB1 closely reflect the proliferative activity of cells [18,29] and have been previously associated with recurrence in ER-positive/HER2-negative BC [30,31]. PCNA and POLQ are involved in genomic replication and DNA repair [32,33], and their overexpression has been correlated with poor clinical outcome in BC patients [34,35].…”
Section: Dna Repair Genes As Prognostic Factors In Breast Cancer Subtmentioning
confidence: 99%